Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1177/107602960401000314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Smoking on Platelet Count and Platelet Parameters: An Observation

Abstract: Arterial thrombosis occurs with increased frequency in cigarette smokers. It is believed that disturbance of platelet function, especially aggregation, is the essential mechanism responsible for this pathology. However, the effect of smoking on the quantity of platelets might be another contributing factor. The effect of smoking on platelet count is still controversial. We performed a cross section-al study to compare the platelet count and platelet parameters in Thai police who are smokers and non-smokers. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 4 publications
(8 reference statements)
4
15
0
2
Order By: Relevance
“…Furthermore, while the effect of “smoke” on platelet count remains controversial, with studies showing it to be increased51 or unaffected,52, 53 we sought to examine whether e‐cigarettes would produce any effects under our experimental conditions. Our data revealed no difference in platelet count between clean air– and e‐cigarette–exposed mice, that is, 526±64 versus 571±96 (thousand/µL; P =0.323), respectively, at least under the present experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while the effect of “smoke” on platelet count remains controversial, with studies showing it to be increased51 or unaffected,52, 53 we sought to examine whether e‐cigarettes would produce any effects under our experimental conditions. Our data revealed no difference in platelet count between clean air– and e‐cigarette–exposed mice, that is, 526±64 versus 571±96 (thousand/µL; P =0.323), respectively, at least under the present experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with our hemostasis findings, as a (significant) decrease in platelet count would be expected to result in a bleeding diathesis, and not the shortened bleeding time we observed. As for the effects of traditional tobacco, studies are controversial, with some showing the platelet counts to be increased51 or unaffected 52, 53. These differences could be attributed, in part, to the different exposure conditions and study populations/subjects.…”
Section: Discussionmentioning
confidence: 99%
“…PLR, however, was not related to smoking [23] in the general population, and neither was platelet count in this study. Lack of evidence for an association between platelet count and smoking has been reported more often [25,26], though lower platelet levels in smokers have also been observed [27,28].…”
mentioning
confidence: 99%
“…Brumit and Baker found no correlation between platelet count and smoking in healthy volunteers (Brumit and Baker, 2000). Also Dotevall et al noted no changes in platelet count in female smokers and non-smokers (Dotevall et al, 1992), and Suwansaksri et al observed no alteration in platelet in smokers and non-smokers (Suwansaksri et al, 2004). According to Blann et al, smoking two cigarettes a day by chronic smokers of both sexes does not affect the platelet count (Blann et al, 1998).…”
Section: Discussionmentioning
confidence: 97%